Associations of tumor necrosis factor-α polymorphisms with the risk of colorectal cancer: a meta-analysis. Issue 1 (11th January 2019) - Huang, Xue; Qin, Shanyu; Liu, Yongru; Tao, Lin; Jiang, Haixing
Abstract : Background: Recently, the roles of tumor necrosis factor-α ( TNF-α ) polymorphisms in colorectal cancer (CRC) were analyzed by some pilot studies, with inconsistent results. Therefore, we performed the present study to better assess the relationship between TNF-α polymorphisms and the risk of CRC. Methods: Eligible studies were searched in PubMed, Medline, Embase and CNKI. Odds ratios (ORs) and 95% confidence intervals (CIs) were used to assess correlations between TNF-α polymorphisms and CRC. Results: A total of 22 studies were included for analyses. A significant association with the risk of CRC was detected for TNF-α -308 G/A (recessive model: P = 0.004, OR = 1.42, 95%CI 1.12–1.79) polymorphism in overall analyses. Further subgroup analyses based on ethnicity of participants revealed that TNF-α -238 G/A was significantly correlated with the risk of CRC in Caucasians (dominant model: P = 0.01, OR = 0.47, 95%CI 0.26–0.86; overdominant model: P = 0.01, OR = 2.27, 95%CI 1.20–4.30; allele model: P = 0.02, OR = 0.51, 95%CI 0.29–0.90), while -308 G/A polymorphism was significantly correlated with the risk of CRC in Asians (recessive model: P = 0.001, OR = 2.23, 95%CI 1.38–3.63). Conclusions: Our findings indicated that TNF-α -238 G/A polymorphism may serve as a potential biological marker for CRC in Caucasians, and TNF-α -308 G/A polymorphism may serve as a potential biological marker for CRC in Asians.